PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marbun, Ervina; L. Tobing, Vargo Christian (EDUTECH CONSULTANT, 2020)
The company was founded aiming to achieve maximum profit, to improve the welfare of shareholders, through the company's ability to pay dividends. The company invest their funds to get high dividends, so potential investors are interested in investing. The number of investors who want to invest in a company affects the company's stock price. The value of the company's shares is shown as the value of the company. This study aims to determine the effect of managerial ownership, institutional ownership, and leverage on firm value. The study population consisted of 72 companies in the basic industrial and chemical sectors which were listed on the Indonesia Stock Exchange in the 2014-2018 period. The research sampling technique used a purposive sampling method to obtain 55 companies that met the criteria. This research data is secondary data from annual financial statements. The method of data analysis uses multiple regression analysis. F test results indicate that managerial ownership, institutional ownership, and leverage simultaneously affect the value of the company. T test results show managerial ownership and leverage do not have a significant effect on firm value.